Progress of treatment and resource utilization for high salinity printing and dyeing wastewater based on bibliometric study - Wang, Qiannan; Zhang, Xiaojiao (Frontiers in Environmental Science, 2025)
The treatment or resource utilization of high-salinity wastewater from printing and dyeing has received great attention in recent decades due to their negative impacts on the surrounding environment. To improve the direction of research, we analyzed the published papers in the online version of the Science Citation Index Expanded database for 1991–2022—a total of 1090 articles or reviews—using VOSviewer, Python, origin 2023, and the statistical software R. The results showed that the published papers in this field have increased exponentially in the past 17 years. The Journal of Membrane Science, Desalination, the Chemical Engineering Journal, and the Journal of Hazardous Materials are the most important for publishing relevant research. Van Der Bruggen B was the most productive author. Katholieke University Leuven and Donghua University were the main research institutions. There were additional needs to enhance collaboration relationships between different authors, institutions, and countries. At present, research focused on methods that are closer to “real” field or ground conditions, “photocatalysis,” “loose nanofiltration membranes”, and “dye/salt separation” are the research frontier. The present study determines the trends of this field of research by visualizing the current landscape to facilitate future collaborative research.